Recovery of Precious Metals from Chloride Solution by Magnetite - Alorro, Richard; Hiroyoshi, N.; Ito, M.; Tsunekawa, M. (AusIMM, 2010)
The development of environmental-friendly lixiviants as alternatives to cyanide and the increasing recycling activities to recover precious metals from waste materials have prompted researchers to find efficient methods and alternative sorbents to recover precious metals, such as Au and Pt, from aqueous solutions. This study explored the use of magnetite (Fe3O4) as a sorbent to recover Au and Pt from chloride solutions. Magnetite is a semiconductor and has the capability of transferring electrons both within the solid state and across the solid-liquid interface and has the ability to reduce metal species on its surface. The sorption of AuCl4- and PtCl62- from NaCl solution on commercial grade magnetite powder was investigated by batch-sorption experiments. The effects of pH, contact time, NaCl concentration and precious metal concentration on the recovery were studied. Sorption experiments revealed that magnetite exhibited selectivity towards other metals with the strongest affinity for Au. Both Au and Pt recoveries showed similar pH dependence curves, with peaks at pH 6-7. At this pH range, a maximum of 4.4 µmol Au/g Fe3O4 and 3.0 µmol Pt/g Fe3O4 were recovered after 24 h at an initial metal concentration of 0.05 mol/m3. Increasing the initial precious metal concentration increased the Au and Pt uptake amount by magnetite. It was also observed that the recovery decreased with high NaCl concentrations. The SEM images of the magnetite particles after the treatment showed that gold, which was confirmed by the EDX analysis, agglomerated and were deposited on Fe3O4 surface.